National and Regional Fraction of Cancer Incidence and Death Attributable to Current Tobacco and Water-Pipe Smoking in the Eastern Mediterranean Countries in 2020. Issue 1 (27th July 2022) - Nemati, Saeed; Naji, Parnian; Abdi, Sepideh; Lotfi, Fereshte; Saeedi, Elnaz; Mehravar, Sepideh A; Fattahi, Pedram; Sheikh, Mahdi; Vand Rajabpour, Mojtaba; Eftekharzadeh, Anita; Zendehdel, Kazem
Abstract: Introduction: We aimed to calculate the Population Attributable Fraction (PAF) of cancers due to tobacco use in the Eastern Mediterranean Region (EMRO), where water-pipe smoking is prevalent but its effect was not considered in previous studies. Aims and Methods: We applied Levin's formula to estimate PAFs of cancers due to tobacco use (defined as all type tobacco including both cigarette and water-pipe). We also calculated PAF of water-pipe smoking separately. Exposure prevalence data were retrieved from representative national and subnational surveys. Data on cancer incidence and death were also and cancer cases were obtained GLOBOCAN 2020. We also obtained associated relative risks from published meta-analyses. Results: Of the total 715 658 incident adult cancer cases that were reported in 2020 in EMRO, 14.6% ( n = 104 800) was attributable to tobacco smoking (26.9% [ n = 92 753]) in men versus 3.3% ( n = 12 048) in women. Further, 1.0% of incident adult cancers were attributable to current water-pipe use ( n = 6825) (1.7% [ n = 5568]) in men versus 0.4% ( n = 1257 in women). Conclusions: PAFs of cancers due to tobacco smoking in EMRO were higher in our study than previous reports. This could be due to the neglected role of water-pipe in previous studies that is a common tobacco smoking method in EMRO. The proportion of cancers attributable to water-pipe smoking in EMRO might be underestimated due to lack of research on the risk of cancers associated with water-pipe smoking and also less developed cancer registries in EMRO. Implications: In this study, we found higher PAFs for cancers due to tobacco smoking in the Eastern Mediterranean (EMR) region than previous reports. This difference could be due to ignoring the role of water-pipe smoking in previous studies. In 2020, 1% of incident cancers and 1.3% of cancer-related deaths in EMRO were attributable to water-pipe smoking. We also found a big difference in PAFs of cancers due to tobacco and water-pipe smoking across EMRO countries, with Tunisia, Lebanon, and Jordan having the highest, and Djibouti, Sudan, and Somalia having the lowest proportions of cancers attributable to tobacco and water-pipe smoking.